If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t = 14 + -2t Solving t = 14 + -2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2t' to each side of the equation. t + 2t = 14 + -2t + 2t Combine like terms: t + 2t = 3t 3t = 14 + -2t + 2t Combine like terms: -2t + 2t = 0 3t = 14 + 0 3t = 14 Divide each side by '3'. t = 4.666666667 Simplifying t = 4.666666667
| 4t=15-13t | | x^3+3x^2-24x-3=0 | | 7n+26=5n | | 6.1+10.1q=4q | | 13p+54=7p | | 3x^3-15x^2+21x-5=0 | | 0.3c=25.9+4c | | 8.4d-23=13d | | 71-12=9a | | 4x-6=7x+3 | | x-(a+3)=a-2(a-x) | | 192-7x=29x+16 | | x^8-6x^6=0 | | 11-9x=128-30x | | 223+175= | | 123+175= | | x^4+2x^3+x^2=0 | | -15-6x=5-10x | | 5x-7=2x+3x-7 | | 4x^2=36x | | 490-x=23 | | 2h+3h^2-2h^3=2 | | 2h+3h^2-2h^3=3 | | -5x=8 | | 8g=5g-21 | | 17a=4a-9 | | 3g+17.2=11.6g | | 49-3x=6x+19 | | 5n=53-2.6n | | 6p=60-4p | | 4a+13=69-4a | | 4y=56.7-2.3y |